锥齿轮测量齿面接触分析方法研究 - 张卫青; 郭晓东; 张明德; 翟庆富 (Jixie chuandong)
The real tooth contact zone of spiral bevel gear is usually different with the theoretic result, effected by machining error and heat treatment distortion. In this paper, two TCA （Tooth Contact analysis） methods of measured tooth surface is putted forward. And a calculate programm is developed based on UG platform. In the end, a calculation example is carried out. The result show that both two methods can achieve the TCA of measured tooth surface.